An interesting clinical association of short neck with an unusual laryngeal anomaly - Pinninti, Rakesh (Medknow Publications & Media Pvt Ltd, 2011)
An elongated high-rising epiglottis can represent a normal variation of the larynx in a majority of pediatric patients. However, there are virtually no reports available for visible or high-rising epiglottis on routine oral examination in adult patients without upper respiratory tract inflammation. We report an unusual case with prominently visible epiglottis on oral examination. We diagnosed him with a rare congenital disorder based on associated physical examination and imaging evidence of short neck, low hair line, Sprengel's anomaly, left digital hypoplasia, restricted neck movements, cervical vertebra fusion, and mirror movements (synkinesia).